The Existence and Implementation of Customary Law in Acehnese Society Viewed from a Juridical Perspective - Sitompul, Theodore Daniel; Rahmadia, Mohamad Haikal; Suparba, Raden Dzaky Muhtadi Abhista; Fasya Akbar, Muhammad Rayhan; Fadhilah, Muhamad Arif; Aulia, Fara; Mulyadi, Mulyadi (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
This research examines the existence and implementation of customary law in Acehnese society through a normative juridical approach. Aceh is a province whose capital is Banda Aceh, and is located at the northern tip of the island of Sumatra. Aceh has a long history as a center for the spread, culture and religion of Islam in Indonesia, so it is called the "Veranda of Mecca" which differentiates it from other provinces in Indonesia. Researchers use qualitative engineering research methods which aim to analyze the topics discussed and relate them to applicable cases or laws. Research findings reveal that customary law still has significant power and relevance in resolving conflicts, maintaining traditions, and regulating the social life of the Acehnese people. However, challenges in implementing customary law were also identified, including harmonization with national legal systems and social and economic changes. Therefore, this research presents a comprehensive picture of how customary law interacts with the modern legal system in Aceh and its juridical implications for Acehnese society.